Wairua, Affect and National Days Project (Website Design) - Muriwai, EM (http://www.wairuaaffectnationaldays.info/)
‘Race’, culture, and nationhood are continually reproduced in both daily activities and key events, through embodied social meanings and practices. Our research project explores little-studied acts of commemoration/celebration that express nation and community. Waitangi Day, Anzac Day, Matariki, Chinese and Gregorian New Year, build and divide, acknowledge and deny, include and exclude and are focal points where we represent ourselves to each other and the world. They are rich in meaning, wairua and emotion for all citizens, whether participating directly or not and have major implications for identity, wellbeing and social cohesion. Our research focuses on the affective politics evoked as people relate, engage and grapple with cultural observances and often-charged acts of remembrance in Aotearoa New Zealand. We are producing new conceptual knowledge around wairua and affect as neglected dimensions of relationships between Māori and non-Māori. Innovative methods have been produced in a convergence of kaupapa Māori and affect theory approaches, using multiple qualitative techniques to gather rich, diverse, multimodal data from Māori and non-Māori. The project is a strong collaboration between Māori and non-Māori team members that is training two doctoral students and building new theory, method and research capability in a cutting edge investigation of great salience to national life in Aotearoa New Zealand.